2013
DOI: 10.1590/1516-4446-2012-0797
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and other markers of cardiovascular risk during a manic episode in patients with bipolar disorder

Abstract: Objective: To evaluate serum levels of different biomarkers associated with cardiovascular disease in patients with bipolar disorder (BD). Patients were prospectively evaluated in two separate instances: during acute mania and after remission of manic symptoms. All measurements were compared with those of healthy controls. Methods: The study included 30 patients with BD and 30 healthy controls, matched for gender and age. Biochemical parameters evaluated included homocysteine (Hcy), folic acid, vitamin B12, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In this study, BD patients had significantly higher prevalence of HHcy and greater plasma Hcy levels, which was consistent with the majority of previous studies assessing HHcy (Ezzaher et al, 2011;Permoda-Osip et al, 2013) and detecting Hcy levels in acute bipolar depressive episode (Chiarani et al, 2013;Salagre et al, 2017) and in remission (Chiarani et al, 2013;Dittmann et al, 2007) of BD. Furthermore, we found sex differences in HHcy rates and Hcy concentrations in BD patients, which was in agreement with previous studies showing elevated Hcy levels and HHcy rates in male patients compared with both their corresponding healthy controls and female patients; however, no significant difference was noted between BD women and female controls (Levine, Sela, Osher, & Belmaker, 2005;Osher et al, 2004;Permoda-Osip et al, 2013;Permoda-Osip et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, BD patients had significantly higher prevalence of HHcy and greater plasma Hcy levels, which was consistent with the majority of previous studies assessing HHcy (Ezzaher et al, 2011;Permoda-Osip et al, 2013) and detecting Hcy levels in acute bipolar depressive episode (Chiarani et al, 2013;Salagre et al, 2017) and in remission (Chiarani et al, 2013;Dittmann et al, 2007) of BD. Furthermore, we found sex differences in HHcy rates and Hcy concentrations in BD patients, which was in agreement with previous studies showing elevated Hcy levels and HHcy rates in male patients compared with both their corresponding healthy controls and female patients; however, no significant difference was noted between BD women and female controls (Levine, Sela, Osher, & Belmaker, 2005;Osher et al, 2004;Permoda-Osip et al, 2013;Permoda-Osip et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Peripheral homocysteine (Hcy) has been considered as a potential biomarker for bipolar disorder (BD; Ghanizadeh, Singh, Berk, & Torabi‐Nami, ; Salagre et al, ). BD patients with hyperhomocysteinemia (HHcy) usually show abnormally high levels of Hcy in the blood (Chiarani et al, ; Dittmann et al, ; Osher, Bersudsky, Silver, Sela, & Belmaker, ; Osher, Sela, Levine, & Belmaker, ), which could increase the risk of cardiovascular disease (Chiarani et al, ). Some previous review articles have repeatedly described sex differences in prevalence, symptom characteristics, and disease outcome in BD (Baskaran, Cha, Powell, Jalil, & McIntyre, ; Bauer, Glenn, Pilhatsch, Pfennig, & Whybrow, ; Gogos, Ney, Seymour, Van Rheenen, & Felmingham, ; Jogia, Dima, & Frangou, ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Large, epidemiological studies have consistently found an increased risk of cardiovascular mortality in bipolar disorder, approximately twice that expected on the basis of age and gender. 2 This risk is higher in bipolar I disorder, which conveys a greater burden of manic and hypomanic symptomatology, than in bipolar II disorder.…”
mentioning
confidence: 98%
“…1 No biomarkers associated with cardiovascular risk were associated with mania, apart from reductions in ferritin, an acute phase reactant. It is not clear how to interpret this finding.…”
mentioning
confidence: 99%
See 1 more Smart Citation